The Correlation of Calcium and Hemoglobin Level Among Pregnant Women in ≥35 Weeks with the Anthropometry of Newborn Babies - Hendraswari CA; Pramatirta AY; Susiarno H; Hilmanto D; Zuhairini Y; Sahiratmadja E (International Journal of Women's Health)
Chatrine Aprilia Hendraswari,1,* Akhmad Yogi Pramatirta,2,* Hadi Susiarno,2 Dany Hilmanto,3 Yenni Zuhairini,4 Edhyana Sahiratmadja5,* 1Program Study of Midwifery, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia; 3Department of Pediatric, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 4Department of Public Health, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 5Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia*These authors contributed equally to this workCorrespondence: Akhmad Yogi Pramatirta, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran/Dr Hasan Sadikin General Hospital, Jalan Raya Bandung-Sumedang Km. 21, Jatinangor, Bandung, West Java, 45363, Indonesia, Tel +62 813-2040-3090, Email akhmad.yogi@unpad.ac.idBackground: Low birth length and low birth weight can be caused by nutritional deficiencies in pregnant women, including calcium and iron deficiency anemia because it retards fetal growth during pregnancy. This study aimed to explore the correlation between calcium and hemoglobin levels in third-trimester pregnant women with anthropometry of newborn babies.Methods: This study employed a prospective cohort design, including 120 third-trimester among pregnant women in ≥ 35 weeks and their newborn aterm babies, using a convenience sampling technique. This study was conducted in March–May 2024. Data on complete blood count tests and calcium levels of the mothers were collected, and anthropometry of newborn including birth length and birth weight was measured. Data were analyzed using univariate, bivariate, and multivariate analysis.Results: The mean maternal calcium and hemoglobin levels were 2.19 mmol/L (sd 0.135) and 11.55 gr/dL (sd 1.187), respectively. The mean birth weight and median birth length were 3.02 kg (sd 0.374) and newborn’s length 48.29 (sd 1.86), respectively. There was a positive correlation between calcium levels (p=0.007; r=0.246), as well as between hemoglobin levels (p=0.006; r=0.25) of pregnant women and the length of newborn babies. Furthermore, hemoglobin level was also correlated with the weight the newborns (p=0.001; r=0.29).Conclusion: Low calcium level and low hemoglobin level among pregnant women in third trimester tend to have short-born babies. In addition, low hemoglobin level is more likely to have low birth weight. Therefore, it is necessary to monitor the provision of calcium and iron supplements as an alternative, after prioritizing the consumption of natural foods.Keywords: birth length, birth weight, calcium, hemoglobin, iron